THE PATENT LICENSING CONUNDRUM: A SUBSTANTIAL BRAZILIAN LEGAL THEORY IN THE LAW OF CONTRACTS - Feres, Marcos Vinício Chein; Silva, Denis Franco (Revista Ética e Filosofia Política, 2018)
Much of the discourse theory has been used to promote the proper application of the law. Much effort has been made in order to look deeper into legal theory. However, very little legal philosophical research has been done so as to shed light on a specific field of law. Contract Law has a natural appeal for instrumental rationality, for the underpinnings of a contractual relationship are based on a consensus derived from strategical action. Is it possible to apply discourse theory to the understanding of a contract of transfer of technology? How can entrepreneurial policies be effective in the marketplace despite a basic moral argument – the dialectical relation between public and private autonomy? In this vein, the intent of this paper is to articulate public intervention in a contract without jeopardizing private autonomy. The discourse theory, as the theoretical point of departure of this work, is not a transcript either of Habermasian communicative theory or Dworkin’s argumentation theory. In fact, both of these authors are responsible for the legal theory conception which conveys a new approach on the hermeneutics of economic law, mainly the contracts of transfer of technology. The Brazilian Intellectual Property Rights Act states, firstly, that the bearer of patent rights can celebrate a contract in which is licensed the use and exploitation of the patent, and secondly, further on, that the bearer will be deprived of his (her) rights if he (she) abuses them or abuses his (her) market’s economic power. A patent is an important means of achieving economic efficiency in the market. Although it is essential for scientific development to grant privileges to inventor in order to avoid unauthorized copies, it is necessary to control this special case of monopoly. In this context, is public intervention in this contract a matter of principle or a matter of policy? Is compulsory licensing by the Brazilian government instituted against Efavirenz – used in the treatment of AIDS – a matter of policy or a matter of principle? First of all, an item will be dedicated to the study of the application of discourse theory to private autonomy. Then, limits to contract law will be interpreted according to this theory. Thirdly, the case of patent law and its different licensing approaches is elaborated departing from this new paradigm of contract law. Finally, a substantial legal theory can be deduced from the specific Brazilian patent conundrum.